IMPLEMENTASI ENVIRONMENTAL AWARENESS, ENVIRONMENTAL INVOLVEMENT, ENVIRONMENTAL REPORTING, DAN ENVIRONMENTAL AUDIT TERHADAP CORPORATE SOCIAL RESPONSIBILITY (Rumah Potong Ayam Tri Susanti) - Restiana, Diva Naja; Budiantara, Martinus (ITB AAS Indonesia Surakarta, 2024)
This research aims to describe the implementation of Corporate Social Responsibility (CSR) based on Environmental Awareness, Environmental Involvement, Environmental Reporting, and Environmental Audit at the Tri Susanti Chicken Slaughterhouse (RPA). This research uses qualitative methods with a descriptive nature. The approach uses primary data sources obtained directly from observations and interviews as well as secondary data in the form of financial report documents. The results of the research conducted show that the implementation of CSR in RPA Tri Susanti has not been fully implemented, but several aspects of the implementation stage have been carried out. Environmental reporting in RPA Tri Susanti is still carried out by presenting environmental costs as expenses outside the business and reducing company profits in the Profit and Loss Report. In this research, researchers have made improvements to the financial reports related to recording CSR costs in the Tri Susanti RPA. With improvements in recording financial reports, business actors feel helped because they can be used to improve the implementation of green accounting based on Environmental Awareness, Environmental Involvement, Environmental Reporting and Environmental Audit in order to create sustainable businesses that are friendly to the environment.